Investigation of Chained Process Quality for Product Design Using FEM and Experimental Verification - bin Kasim, Khairulnizam; bin Mohd Saman, Alias; HP Manurung, Yupiter; Muhammad, Norasiah; bin Zainul Abidin, Azrriq; Faris Asyraaf bin Shaari, Ahmad; ., . (International Journal of Engineering and Technology, 2018)
In this research, chained process simulation is to be investigated to solve the major problem of component distortion which is commonly occurred and cannot be neglected in fabrication process. Stamping-welding as coupled process is the main concern to be reassembled into simulation under consideration of property history transferred from previous process. The selected component geometry is rear arm as parts of automotive steering structure made of material SPH440 and STKM13A. The FEM simulation starts with the modeling of real components and executed based on actual hydraulic stamping followed by GMAW process parameters. In both simulation processes, nonlinear isotropic hardening model was used taken from existing software database of equivalent material properties. The experimental investigation is conducted for verification purpose. The conclusion can be drawn throughout the research that the specialized FEM software Simufact Forming and Simufact Welding had outstanding capability to predict final distortion for complex chained processes with complex geometry.Â Â